2017
DOI: 10.1002/2016wr019983
|View full text |Cite
|
Sign up to set email alerts
|

Heat and water transport in soils and across the soil‐atmosphere interface: 2. Numerical analysis

Abstract: In an accompanying paper, we presented an overview of a wide variety of modeling concepts, varying in complexity, used to describe evaporation from soil. Using theoretical analyses, we explained the simplifications and parameterizations in the different approaches. In this paper, we numerically evaluate the consequences of these simplifications and parameterizations. Two sets of simulations were performed. The first set investigates lateral variations in vertical fluxes, which emerge from both homogeneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…Although the Richards equation models are mostly employed in a form that only considers isothermal liquid water flow, it should be noted that the heat transfer is coupled with water flow in all these three models in this study to provide a consistent comparison. In addition, even though lateral water flow has been ignored in some models, it has been indicated that the lateral flow has an effect on the fluxes within the soil profiles and also at the soil-atmosphere interface (Fetzer et al 2017) and therefore is considered in all the three models.…”
Section: Numerical Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the Richards equation models are mostly employed in a form that only considers isothermal liquid water flow, it should be noted that the heat transfer is coupled with water flow in all these three models in this study to provide a consistent comparison. In addition, even though lateral water flow has been ignored in some models, it has been indicated that the lateral flow has an effect on the fluxes within the soil profiles and also at the soil-atmosphere interface (Fetzer et al 2017) and therefore is considered in all the three models.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Defining the thickness of the top surface layer is a problem as the soil resistance parameter is highly dependent on the chosen thickness. Interested readers can refer to Fetzer et al (2017) for more discussions on the effect of the chosen top layer thickness on the simulation results. Equations 9 and 14 are referred to as Top Boundary Condition 1 and 2 (TBC 1 and TBC 2) in the following analysis.…”
Section: Top Boundary Conditions (Tbcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…A state‐of‐the‐art review by Vanderborght et al () suggests further that the coupled water and heat transport processes in the soil remains local (for homogeneous medium) and one‐dimensional. In a complementary effort, Fetzer et al () provided numerical analysis showcasing the variations in lateral and vertical water and heat fluxes for simplified heterogeneous (two‐soil) systems. In this paper we revisited some of these available modeling concepts (Vanderborght et al, ) and propose a new and more general multiphysics multidimensional model accounting for soil heterogeneity in water as well as in vapor flows.…”
Section: Introductionmentioning
confidence: 99%